Analysis of Women’s Consumer Perception of Contemporary Fashion Based on Kediri Weaving Wastra - Soelistyowati Soelistyowati; Enrico Enrico (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study is motivated by the low visibility and limited acceptance of Kediri woven textiles among younger generations, despite their strong cultural, aesthetic, and historical value. The objective of this research is to analyze consumer perceptions, perceived value, and factors influencing purchase decisions among young consumers toward Kediri weaving–based fashion, as well as to formulate appropriate design and branding strategies aligned with contemporary market needs. A qualitative case study approach was employed through in-depth interviews, focus group discussions, observations, and social media analysis involving 25 female informants aged 18–35 years. The findings reveal that young consumers hold positive perceptions of the cultural and aesthetic value of Kediri weaving. However, purchase intentions are hindered by limited design variation, perceptions of traditional rigidity, and relatively high prices. These findings indicate a gap between the cultural value embedded in the product and the lifestyle expectations of young consumers. The study implies that design innovation, storytelling strategies, and value proposition alignment combined with cost efficiency are essential to enhance product competitiveness. Kediri woven textiles have strong potential to be repositioned as contemporary fashion products when redesigned through a culturally grounded yet youth-oriented approach that integrates heritage values with modern consumer preferences.